A Study Of Flow Characteristics Along The Hydraulic Physical Model Of Kenyir Dam Spillway - Manogaran, Thiennieesh (Universiti Sains Malaysia, 2021)
Water flowing over a spillway has a very high kinetic energy because of the conversion of the entire potential energy to the kinetic energy. This circumstance will result in damage or significant erosion at the toes of the spillways, the weir bed, and downstream of a river. To solve this problem, the water flow velocity must be minimised. Physical modelling was implemented to this conundrum in order to modify the current energy dissipating structure, the stilling basin, to enhance energy dissipation as much as achievable by downstream velocity reduction. The baffles blocks were adopted as the modification in this study because they are widely used to stabilise the jumps, shorten its length, and maximise energy dissipation. A selection of baffle arrangements was evaluated by positioning them in the stilling basin's mid-span to identify the most effective outcome in minimising downstream velocity. From the findings, it is clearly shown arrangement of baffles blocks at the stilling basin impacts velocity reduction at various discharge cases. The formation of cross-waves was also assessed at the discharge channel at every discharge value with its relative distance from the sump and the width of the channel prior to the site. For discharge situations of 70.0 L/s and 100.0 L/s, modifications to the Type II stilling basin were recommended. Furthermore, constriction, expansion, or curvature should be avoided in chute spillways identical to the Kenyir Dam spillway to limit cross-wave generation and other unfavourable flow behaviours.